Social Relations, Safety, and Acceptance—Making Meanings of Home in Children’s and Young People’s Visual Expression - Koistinen, Aino-Kaisa; Lähdesmäki, Tuuli; Ylönen, Susanne C. (Journal of Education Culture and Society, 2025)
Aim. This article aims to understand children’s and young people’s notions of home by analysing how children express the meanings they invest in the concept of home both visually and in related explanatory texts. Methods. The article explores outcomes of a creative task implemented in schools in six countries with students aged 5 to 15. The data consists of 559 visual artefacts and captions explaining their contents. In the examination of the data, we engaged in a thematic and contextual qualitative analysis that follows the inductive logic of close reading. Results. Our analysis reveals three interlinked meaning-making modes through which the students dealt with the idea of home and identifies key elements that make them feel at home: home as social relations; home as safety; and home as acceptance. For the students, home commonly includes a material dimension, a house, but it becomes “a home” only through meaningful social relations, emotions, and everyday practices. Conclusions. Our findings bring to the fore a rather unified understanding of home, pointing out that there are shared cultural and school-derived conventions that affect the manners in which creative tasks are approached by students in the school context. Yet general conformity also highlights the instances in which expressions of home deviate from expectations, as the depictions of safety as “protection from” exemplify in our data. In these depictions, the nationalistic and exclusionary aspects associated with home are brought to the fore.